2002
DOI: 10.1007/bf03033722
|View full text |Cite
|
Sign up to set email alerts
|

Significance of angiogenesis and microvascular invasion in renal cell carcinoma

Abstract: The aim of this study is to evaluate the relationship between tumor angiogenesis and microvascular invasion, and the subsequent development of metastatic disease in patients undergoing surgery for renal cell carcinoma (RCC). The study group consisted of 102 patients who underwent surgery for RCC between the years 1990 and 1997 in our institute with a mean follow up period of 81.3 months. Paraffin blocks were stained for Factor VIII - related antigen and CD34 which decorate endothelial cells in order to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 37 publications
0
35
1
1
Order By: Relevance
“…Recently, Lisanti and co-workers (Liu et al, 2002) have shown that, within an in vitro model of angiogenesis, the direct delivery of caveolin-1-derived peptides to the cytoplasm of endothelial cells is sufficient to induce capillary tubule formation. These findings are of significance since several independent studies advocate that the presentation of angiogenesis and microvascular invasion in patients who undergo surgery for RCC are at high risk for developing metastatic disease (Van Poppel et al, 1997;Dekel et al, 2002;Griffiths et al, 2002). More work will be required to determine whether or not caveolin-1 immunoreactivity is a useful clinical marker.…”
Section: Discussionmentioning
confidence: 92%
“…Recently, Lisanti and co-workers (Liu et al, 2002) have shown that, within an in vitro model of angiogenesis, the direct delivery of caveolin-1-derived peptides to the cytoplasm of endothelial cells is sufficient to induce capillary tubule formation. These findings are of significance since several independent studies advocate that the presentation of angiogenesis and microvascular invasion in patients who undergo surgery for RCC are at high risk for developing metastatic disease (Van Poppel et al, 1997;Dekel et al, 2002;Griffiths et al, 2002). More work will be required to determine whether or not caveolin-1 immunoreactivity is a useful clinical marker.…”
Section: Discussionmentioning
confidence: 92%
“…Although the detailed molecular mechanism involved in neovascularization in and around the tumor is not fully understood, the angiogenic growth factor vascular permeability factor (VPF)/vascular endothelial growth factor (VEGF)-A appears to play an important role (4). This is also the case for renal cell carcinoma [RCC (5,6)]. RCC is a heterogeneous disease from both phenotypic and genetic points of view.…”
Section: Introductionmentioning
confidence: 99%
“…Radical nephrectomy is the therapy of choice only for the initial stage; there is not yet any established therapeutic approach for the advanced metastatic stage (8). Because angiogenesis has been found to be essential for renal cancer progression (5,6), antiangiogenic therapy, especially in combination with any potential chemotherapeutic agent, will have a promising future in designing an effective therapeutic approach for RCC.…”
Section: Introductionmentioning
confidence: 99%
“…For most of solid tumours, microvessel density (MVD) correlates with poor prognosis. However, MVD remains a controversial prognostic predictor for RCC (Kirkali et al, 2001;Sabo et al, 2001a;Suzuki et al, 2001;Dekel et al, 2002;Kinouchi et al, 2003;Yildiz et al, 2008;Qian et al, 2009), a significant contributory factor being that blood vessels in RCC may be regarded as being monolithic in structure and function, which might not accurately reflect the functional diversity based on microvessel differentiation and location. Mature blood vessels are usually covered by pericytes, and pericyte coverage is regarded as an indicator of vascular maturation (Gerhardt and Semb, 2008).…”
Section: Hai-lun Zhan Xin Gao* Xiang-fu Zhou Xiao-yong Pu De-juanmentioning
confidence: 99%